Transforming Barasuara's “Guna Manusia” into brass band adaptation and sociocultural impact - Ganang Dwi Asmoro; Agam Maha Putra Alhakim (Universitas Pendidikan Indonesia, 2023)
This study examines transforming Barasuara's